Oderwanie przyczepu piszczelowego więzadła krzyżowego – rzadkie i ważne zagadnienie - Tramś, Marek; Wlazło, Magdalena; Tramś, Ewa; Pietrzyk, Justyna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
The tibial spine fractures occurs mainly in children and adolescents because the tibial intercondylar eminence is not completely ossified. It is believed that the tibial spine fractures are correspondent to the more frequent anterior cruciate ligament injury in adults. Treatment depends on the degree of fracture. 4-grade Meyers and McKeever scale is the most commonly used method in the classification. Grade I is the least complicated and grade IV is complete fragmentation of the detached element. There are no consistent guidelines or recommendation about various degrees of fracture treatment. Many surgical treatment methods are described. Complications reported in the current literature including arthrofibrosis, non-union, mal-union, pain and severe laxity lead to detailed analysis of available literature and long-term follow-up. Objective: The purpose of this publication is to give information about diagnosis and treatment of the tibial eminence fracture. It is addressed to the doctors, especially paediatricians and paediatric orthopaedics who deal with this issue. Knowledge of this topic is very valuable due to the possible serious complications.